ТАЙВАНИЙ УЛС ТӨР, ЭДИЙН ЗАСГИЙН ХӨГЖИЛ - Э.Саранцэцэг (Politology, 2023)
During the years of attempts to make the Korean coast as the “Little Japan”, the Japanese had an Island in the Southern Chinese sea under their rule. After wards of Manchu occupation of China in the XVII century, a large population of Chinese settled down on the Island migrating from their native land. Being Landed by Portuguese and Dutch earlier, the Island was occupied by Manchu later, and attached to qing Dynasty possession. In 1895 China was defeated by Japan, and as the result of Simonosec agreement China gave the Island to Japanese rule. This small Island, which was subjugated by Japan, found a destiny to grow and to become one of the most powerful economy in Asia, is the nowadays Taiwan.